Faktor-Faktor Yang Mempengaruhi Penggunaan Jasa Transportasi Umum “Trans Sarbagita” (Studi Kasus Mahasiswa Universitas Udayana) - Surung, Ni Putu Diah Wulandari; Arka, Sudarsana (Jurnal Ekonomi Kuantitatif Terapan; 2014: Vol. 7, No. 1, Februari 2014 (pp. 1-82)DO - 10.24843/JEKT.2014.v07.i01.p01)
The operation Trans Sarbagita Bus is one of a transportation project to implement a modern transportation governance with the aim of providing mass transportation facilities and organizing comfortable and futuristic transportation in Bali. The purpose of this study to determine the effect of simultaneous or partially between revenue, cost of transport and accessibility towards the intensity of the use of public transport services Trans Sarbagita. The samples in this study were regular students of Udayana University who use Trans Sarbagita buses, as many as 80 people with accidental sampling method. The analysis technique used is Binary Logistic Regression Model. Results of the data analysis showed, that simultaneously revenues, costs of transport and accessibility have a significant effect towards the intensity of the use of public transport services Trans Sarbagita. Income and accessibility partially negative and significant effect towards the intensity of the use of public transport services Trans Sarbagita, while transport costs partially not significant effect towards the intensity of the use of public transport services Trans Sarbagita. Trans Sarbagita business should adds bulk carriers so as to reach the locations of residential areas to reduce the use of private transport.
Keywords: revenue , cost of transport , accessibility , intensity